2006
DOI: 10.3758/bf03192763
|View full text |Cite
|
Sign up to set email alerts
|

Comparing observational software with paper and pencil for time-sampled data: A field test of Interval Manager (INTMAN)

Abstract: The INTMAN software system was designed to facilitate the collection of time-sampled data in field-based settings. INTMAN has a collection component and an analysis component. The collection component runs on Pocket 165Copyright 2006 Psychonomic Society, Inc.The first author and the first author's not-for-profit institution receive funds from license sales and therefore have a financial interest in the software described in this article. In this article, we describe the Interval Manager (INTMAN) software syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 4 publications
0
17
1
Order By: Relevance
“…The data were analyzed using a 10-s momentary time sample recording system on a personal computer using Procoder DV (Tapp and Walden 2000). Data from Procoder DV was exported into Interval Manager (Tapp et al 2006) for further analysis and calculation of interobserver agreement (IOA).…”
Section: Data Collection and Dependent Measuresmentioning
confidence: 99%
“…The data were analyzed using a 10-s momentary time sample recording system on a personal computer using Procoder DV (Tapp and Walden 2000). Data from Procoder DV was exported into Interval Manager (Tapp et al 2006) for further analysis and calculation of interobserver agreement (IOA).…”
Section: Data Collection and Dependent Measuresmentioning
confidence: 99%
“…Response Measurement, Interobserver Agreement, and Procedural Fidelity All sessions were videotaped and subsequently verbalizations were coded using a 10-s partial interval recording system (Kennedy, 2005). Data were recorded from videotape in real time using INTMAN software downloaded onto hand held personal digital assistants (Tapp et al, 2006) for Charlotte or pencil and paper for Paul. Two independent data collectors scored responding for interobserver agreement (IOA) during no less than 31% of all sessions.…”
Section: Methodsmentioning
confidence: 99%
“…In one study it was found that an electronic time capture tool was a practical and reliable way to collect and analyze T&M data to evaluate multitasking of nurses (Yen et al, 2016). Thus, electronic T&M study tools can be more efficient and accurate than paperpencil methods (Burke et al, 2000;Lopetegui et al, 2014;Schenk et al, 2017;Tapp et al, 2006;Yoon et al, 2015).…”
Section: Introductionmentioning
confidence: 99%